1978
DOI: 10.1302/0301-620x.60b4.361744
|View full text |Cite
|
Sign up to set email alerts
|

Spondylolysis. A skeletal investigation of two population groups

Abstract: The lumbar spines of 485 skeletons of adult South African "Whites" and "Blacks" of both sexes were examined to determine the incidence and morphology of defects in the pars interarticularis. The overall incidence was 3.5%, without significant variation between races and sexes. The incidence of lumbar spina bifida in the whole sample was 1.9%, but was 11.8% in those skeletons with spondylolysis. Some instances of unilateral spondylolysis demonstrated obvious callus formation, suggesting a capability for normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 0 publications
3
35
1
1
Order By: Relevance
“…Although genetic and racial factors may predispose an individual to spondylolysis [13,15,40], the most generally favored theory is that spondylolysis is a fracture caused by mechanical stress, and that the mode of failure is fatigue [6,7,21,29,41,50,51]. The mechanical etiology of this fatigue fracture is controversial, and many experimental studies have been carried out to determine the fatigue strength of the pars interarticularis and to delineate the movements causing failure [1,10,11,12,28,32].…”
mentioning
confidence: 99%
“…Although genetic and racial factors may predispose an individual to spondylolysis [13,15,40], the most generally favored theory is that spondylolysis is a fracture caused by mechanical stress, and that the mode of failure is fatigue [6,7,21,29,41,50,51]. The mechanical etiology of this fatigue fracture is controversial, and many experimental studies have been carried out to determine the fatigue strength of the pars interarticularis and to delineate the movements causing failure [1,10,11,12,28,32].…”
mentioning
confidence: 99%
“…Ásatag eszkimó vázakon 54%-ban fordul elő (Simper 1986), Nagy-Britannia területén az előfordulás gyakorisága 5% alatti (Eisenstein 1978). Józsa (1996) véleménye szerint a Kárpát-medencében élt népek körében ritkán fordult elő.…”
Section: Az Eredmények Megvitatásaunclassified
“…Unilateral spondylolysis is considered to be rare, and it accounts for 3-33 % of all cases of spondylolysis [54]. Patients with unilateral spondylolysis can be symptomatic or asymptomatic.…”
Section: Unilateral Spondylolysismentioning
confidence: 99%
“…Spondylolisthesis associated unilateral spondylolysis seemed to be uncommon, and the degree of slippage was considered to be minimal. Cases of spondylolisthesis with unilateral spondylolysis accompanying a slippage ranging 3-8 mm has been reported [54], and Beutler et al showed unilateral spondylolysis without spondylolisthesis [22].…”
Section: Unilateral Spondylolysismentioning
confidence: 99%